Analisis Pengaruh Performa PageSpeed terhadap Optimasi SEO Website PT. Bmar - Qurrotu A’yun; Paula Dewanti (IKRA-ITH Teknologi Jurnal Sains dan Teknologi, 2026)
The Fourth Industrial Revolution has reshaped the way industries operate by integrating advanced information technologies into nearly every aspect of business. The convergence of physical, digital, and biological systems has created a new landscape where websites serve as a central platform for marketing and promotion. Their ability to reach wide audiences, provide instant access to information, and reduce operational costs makes them highly effective tools for business growth. At the same time, the crowded digital marketplace poses new challenges, particularly in ensuring that Websites remain visible in search engine results. Search Engine Optimization (SEO) has therefore become an essential strategy to secure stronger rankings and sustain audience engagement. Without effective SEO, Websites risk lower visibility, reduced traffic, and limited promotional impact. This study explores the analysis and optimization of SEO practices to improve website performance and enhance competitiveness in today’s fast-evolving digital industry.